Reconstructing African fractured epistemologies for African development - Lajul, Wilfred (Array, 2019)
The task of advancing knowledge on Africa from rural African spaces by urban African researchers confronts two formidable challenges; namely, the preponderance of myths and ‘being as a force’ in the network of rural African gnosis and the contemptuous poise of the urban African researcher against indigenous knowledge systems (IKS). This attitude is the aftermath of colonial efforts at reserving epistemic hegemony and neo¬colonisation by Africans who have been inundated against the possibility of an African knowledge system. The fixation on myths and force by rural agents and western academy-¬derived knowledge system constitute mutually antagonistic power structures with the cumulative effect of stifling efforts at understanding Africa from inside out. This paper focusing on the Yoruba knowledge society employs a reconstructive approach in proposing two paths to the development of a robust African knowledge base by African researchers. The first path argues that rural agents contributing to developing African episteme must disenchant where necessary. The second is directed at the urgency of achieving a consummated decolonisation. While the former path sees the rural moving from a system of myths to the articulation of liberal epistemic system, the latter seeks to nullify the incredulity and contempt urban researchers have about the reality of knowledge in Africa. Knowledge that has the benefit of African originality can thus be consolidated on an open dialogue between urban researchers and rural agents who have direct relations to the deposit of African gnosis pertaining to politics, law, ethics, pharmacognosy, health care, economy and the environment.